A Few Remarks to the Afanasy Nikitin‘s “Journey Beyond Three Seas” (15th Century) - Lifshits, Aleksandr L. (Slavistica Vilnensis, 2024)
The paper is devoted to several nonobvious places in the Afanasy Nikitin’s travel notes “Journey Beyond Three Seas” and proposes to revisit their discussion. The first part of the paper deals with toponyms. Thus, it is explained why Afanasy prefers the Arabic toponym Misyur to Egypt. In the next section attempts are made to interpret the doubtful toponym Myar/Myara, which is usually identified with Baku without sufficient justification, although among other toponyms it would be more appropriate to see in this name a distorted Myakka – Mecca. Then a new localization of the country of Shabat and the Shabait shelter of the Indian Sea on the map of the Indian peninsula is proposed, which connects geographical realities with the ethno-political context of the Bengal Sultanate. Further in the article, based on an analysis of the text, an assumption is made about which books might have been lost by Afanasy, on what the traveler’s lamentations about their absence are based, and why they could not have helped Afanasy to celebrate Christian holidays on time. It is proved that Afanasy can be considered as an “unbalanced bilingual,” since the text of the notes reflects the process of his loss of a sense of language. It is justified that the preserved version of the notes was created later, almost at the end of the journey.